2003
DOI: 10.1590/s0074-02762003000300007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative immunological recognition of proteins from New Guinea "C" dengue virus type 2 prototype and from a dengue virus type 2 strain isolated in the State of Rio de Janeiro, Brazil

Abstract: The protein profiles of the New Guinea "C" dengue virus type 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…Several authors have reported a significant antibody response to NS3 in both primary and secondary infections (Churdboonchart et al 1991, Valdes et al 2000, Cortes et al 2003. In contrast, a low but significant and specific antibody response to NS3 in 79% of the confirmed dengue cases was observed in this study, and none of the sera from healthy individuals was able to recognize this protein.…”
contrasting
confidence: 87%
See 1 more Smart Citation
“…Several authors have reported a significant antibody response to NS3 in both primary and secondary infections (Churdboonchart et al 1991, Valdes et al 2000, Cortes et al 2003. In contrast, a low but significant and specific antibody response to NS3 in 79% of the confirmed dengue cases was observed in this study, and none of the sera from healthy individuals was able to recognize this protein.…”
contrasting
confidence: 87%
“…Later the same group of researchers (AbuBakar et al 2002) demonstrated, using infected A. albopictus (C6/36) mosquito cells as antigen, antibody responses to the antigenic intermediate core protein (C)-prM and to the nonstructural proteins NS1 and NS2A. Cortes et al (2003) evaluated antibody recognition profiles of DENV-2 (Rio de Janeiro isolated) and DENV-2 NGC proteins and specific recognition for proteins NS3, E, NS1, C, and prM was detected. It is clear that the antigen quality and origin will produce different results, and some antibody responses to some viral proteins may not be detected.…”
Section: Introductionmentioning
confidence: 99%
“…A good correlation between the results of immunoblot strips and type-specific RT-PCR was observed in primary infections (see below) [54]. Other immunoblot kits for dengue diagnosis have been available for several years [3,47,55,56], despite being usually unable to detect antibodies to the NS1 protein in primary infections. A recent report demonstrated the detection of dengue NS1 antigen in serum or plasma in the absence of anti-dengue IgM antibodies, with some advantages over RT-PCR (see section on PCR-based techniques), namely the possibility of storing the samples at 4 C for retrospective testing and the absence of contamination due to the higher stability of antigens [57].…”
Section: Dot-blot Immunoassaymentioning
confidence: 85%
“…NS3 protein plays a predominant role in the pathogenesis of the disease and together with its role during the processing of the precursor of the viral polyprotein makes it an interesting protein for evaluating host responses. Some authors have reported a significant antibody response to NS3 in both primary and secondary infections [3941]. However, Valdes et al, 2000 [40], showed a significant antibody response in secondary cases when the infecting serotype was DEN2.…”
Section: Discussionmentioning
confidence: 99%